Evaluation of the Psychometric Properties of the Scale A-ONE: An Italian Cross-Sectional Study - Margherita Cerone; Marco Tofani; Giovanni Fabbrini; Giulia Marcellini; Anna Berardi; Claudia Conti; Rita De Santis; Donatella Valente; Giovanni Galeoto (Occupational Therapy International)
Purpose. This study is aimed at validating the A-ONE scale in an Italian population with Central Nervous System (CNS) dysfunction. Material and Methods. Between May and November 2018, people aged between 60 and 90 with CNS dysfunction were recruited in a hospital in Rome, Italy. Patients were observed and evaluated during the activities of daily living. Internal consistency and reliability were evaluated with Cronbach’s coefficient alpha and intraclass correlation coefficient, respectively. As measured with Pearson’s correlation coefficient, the validity was examined comparing results of the A-ONE with the Barthel index. Responsiveness was evaluated 30 days after the first administration. Results. A total of 70 people having a diagnosis of neurological disorders were evaluated. The internal consistency showed Cronbach’s coefficient alpha ranging from 0.634 to 0.959. The measurement of reliability varied from 0.984 to 0.997 for intrarater and from 0.979 to 0.998 for interrater. Pearson’s correlation coefficient between the A-ONE and the Barthel index and the responsiveness showed statistically significant values (p<0.01). Conclusions. The present study provides preliminary evidence of reliability, validity, and responsiveness of the A-ONE when using elderly people with CNS dysfunction.